Improvement of Scientific Attitudes Through Training of Social Science Scientific Writing in MAN 2 Model Banjarmasin - Mutiani Mutiani; Heri Susanto; Muhammad Adhitya Hidayat Putra; Helmi Akmal; Jumriani Jumariani (Universitas Lambung Mangkurat, 2020)
Scientific works are essays containing scientific ideas that are presented scientifically and use scientific forms and language. Scientific writing brings up scientific problems that are focused on one particular discipline. This article aims to describe the implementation of scientific paper writing training for students in MAN 2 Model Banjarmasin. So that led to the scientific attitude of the writing team. The lecture and assignment methods were carried out during the training from 24 February to 09 March 2020. The results of the service were presented that writing scientific papers, writers must understand the stages of work; first, make ideas in thought. This idea emerged from the reference book, as well as the results of discussions with colleagues. Second, the writer must express his ideas in narrative form (writing). The work process between stages one and two varies greatly for each author. This matter is influenced by experience and habits. However, the second process has an integrated and systemic stage, so that it can provide clarity on the subject of scientific writing for the writer. The next activity is expected to focus on what social themes are relevant to be written in the form of scientific papers.